2015
DOI: 10.1186/s12864-015-2076-1
|View full text |Cite
|
Sign up to set email alerts
|

Molt-dependent transcriptomic analysis of cement proteins in the barnacle Amphibalanus amphitrite

Abstract: BackgroundA complete understanding of barnacle adhesion remains elusive as the process occurs within and beneath the confines of a rigid calcified shell. Barnacle cement is mainly proteinaceous and several individual proteins have been identified in the hardened cement at the barnacle-substrate interface. Little is known about the molt- and tissue-specific expression of cement protein genes but could offer valuable insight into the complex multi-step processes of barnacle growth and adhesion.MethodsThe main bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…In bioadhesion, peroxidases are known to participate in the catalysis of di-tyrosine formation to post-draw silk fibres produced by the caddisfly larvae (Wang et al 2014), and in the hardening of egg fertilisation membranes of sea urchin (Foerder & Shapiro 1977). It was also found to be present in the adhesive secretions of other organisms such as sea stars, sea urchins, and barnacles (Hennebert et al 2015; Wang et al 2015; Lebesgue et al 2016). The possible functions of peroxidases in the adhesive secreted by Hydra were discussed by Rodrigues et al (Forthcoming), and are similar to the ideas proposed for sea urchins by Lebesgue et al (2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In bioadhesion, peroxidases are known to participate in the catalysis of di-tyrosine formation to post-draw silk fibres produced by the caddisfly larvae (Wang et al 2014), and in the hardening of egg fertilisation membranes of sea urchin (Foerder & Shapiro 1977). It was also found to be present in the adhesive secretions of other organisms such as sea stars, sea urchins, and barnacles (Hennebert et al 2015; Wang et al 2015; Lebesgue et al 2016). The possible functions of peroxidases in the adhesive secreted by Hydra were discussed by Rodrigues et al (Forthcoming), and are similar to the ideas proposed for sea urchins by Lebesgue et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…About 40% of the transcripts expressed in the basal disc had no annotated function and even no orthologue in other metazoans. Novel adhesive proteins were discovered for several organisms, including barnacles, one of the most studied systems (Bacchetti De Gregoris et al 2009; Jonker et al 2014; Wang et al 2015). Already stressed by Jonker et al (2014), more sequence data spanning throughout the metazoan are necessary to identify conserved adhesive domains and gain insight into the relationship between sequence structure and protein function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study attempted to investigate a molt-related transcriptomic response of barnacle cement proteins in different tissues by employing a variety of collection methods and analytical techniques (Wang et al, 2015). Similar to the mass spectrometry (MS) analysis performed in our study, they too had difficulty detecting and identifying cement proteins in their MS analysis.…”
Section: Known Cement Proteinsmentioning
confidence: 99%
“…One proposed explanation was that the cement specific proteins were masked by the presence of more abundant household and scaffold proteins and that the inability to detect the putative adhesive proteins from the uncured material does not necessarily mean that they were not present (Wang et al, 2015). In addition to lacking a standard method to collect the liquid adhesive, they suggested that the limited amount of material that can be collected during a short time period, and the unknown possibility of cross-linking prior to enzymatic digestion for MS analysis (plus the absence of a fully annotated genome), may all contribute to the challenges for the detection of cement proteins in various barnacle secretions (Wang et al, 2015). These rationalizations illustrate the difficulties in detecting cement proteins and provide insight about the overall complexity of this unique and interesting material.…”
Section: Known Cement Proteinsmentioning
confidence: 99%